2022
DOI: 10.32604/cmc.2022.019455
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Encryption Method Using Genetic Algorithm for Key Generation

Abstract: In this new information era, the transfer of data and information has become a very important matter. Transferred data must be kept secured from unauthorized persons using cryptography. The science of cryptography depends not only on complex mathematical models but also on encryption keys. Amino acid encryption is a promising model for data security. In this paper, we propose an amino acid encryption model with two encryption keys. The first key is generated randomly using the genetic algorithm. The second key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Like Sayantani et al [11] they also adopted DNA Transcription and Translation into algorithms to convert the plaintext into DNA bases although their method stayed more true to the biological operations that occur and the components that are used in those operations. Sakr et al [21] used a novel approach for encryption. Their work used genetic algorithm to generate a random security key where randomness was measured using run test of randomness [10].…”
Section: Related Workmentioning
confidence: 99%
“…Like Sayantani et al [11] they also adopted DNA Transcription and Translation into algorithms to convert the plaintext into DNA bases although their method stayed more true to the biological operations that occur and the components that are used in those operations. Sakr et al [21] used a novel approach for encryption. Their work used genetic algorithm to generate a random security key where randomness was measured using run test of randomness [10].…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results showed that the intelligent system of power grid could resist various intrusion behaviors of unknown data sources under the optimization of the algorithm. 11 Song et al combined a MO-GA and a discrete phase model to improve the separator. The experimental results showed that the pressure drop and separation efficiency of the separator were significantly improved under the optimal design of the algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…According to Equation (10), smaller reciprocal means worse fitness value, and lower probability of the risk species for the individual, thus the offspring optimization can be performed. In the crossover calculation of the algorithm, the real numbers of two good parents of the same selection at the j point are crossed to form a new individual, and the crossover operation is expressed as Equation (11).…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations